2021
DOI: 10.3389/fbuil.2021.649224
|View full text |Cite
|
Sign up to set email alerts
|

Critical Response of High-Rise Buildings With Deformation-Concentration Seismic Control System Under Double and Multi Impulses Representing Pulse-Type and Long-Duration Ground Motions

Abstract: The critical responses are investigated for a high-rise building with a deformation-concentration seismic control system under double and multi impulses representing pulse-type and long-duration ground motions, respectively. The critical responses were studied for an elastic-plastic multi-degree-of-freedom (MDOF) shear building model under a double impulse and a multi impulse in the previous papers. However, it seems difficult to derive the critical response for a realistic three-dimensional (3-D) nonlinear fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Palacios-Quinonero et al (2019) applied multiple TMD to inter-storey isolation and adjacent building isolations as illustrated in Figure 3C. Viscous dampers are also applied to adjacent building isolations in Figure 3D by Kasagi et al (2016), Fukumoto and Takewaki (2017), Hayashi et al (2018), Makita et al (2018), Kawai et al (2020Kawai et al ( , 2021, Nakamura et al (2021).…”
Section: Super-structure Isolation Systemsmentioning
confidence: 99%
“…Palacios-Quinonero et al (2019) applied multiple TMD to inter-storey isolation and adjacent building isolations as illustrated in Figure 3C. Viscous dampers are also applied to adjacent building isolations in Figure 3D by Kasagi et al (2016), Fukumoto and Takewaki (2017), Hayashi et al (2018), Makita et al (2018), Kawai et al (2020Kawai et al ( , 2021, Nakamura et al (2021).…”
Section: Super-structure Isolation Systemsmentioning
confidence: 99%
“…(20) Kawai et al (2021) showed that Δt 0.01 [s] is sufficient enough for the accuracy. It is noted that, since a rapid change of input acceleration may cause the occurrence of unbalanced forces, division of the time interval into short durations is often conducted.…”
Section: Critical Double Impulse For Plane Framementioning
confidence: 99%
“…However, their earthquake resilience is not completely guaranteed for longperiod ground motions with a predominant period of 5-8 s (Kamae et al, 2004;Ariga et al, 2006). Although it is believed in general that passive energy dissipating systems (especially connected building systems) are effective for long-duration and long-period ground motions due to allowing sufficient time for energy dissipation (Luco and Barros, 1998;Basili and Angelis, 2007;Takewaki, 2007;Patel and Jangid, 2011;Takewaki et al, 2012;Richardson et al, 2013;Fukumoto and Takewaki, 2015;Kawai et al, 2021), they are not necessarily resilient against impulsive pulse-type ground motions.…”
Section: Introductionmentioning
confidence: 99%